PENGARUH KEPERCAYAAN NASABAH DAN KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH MENABUNG DI BANK RAKYAT INDONESIA CABANG TAPAN - Badri, Juarsa; Sepriyanti, Rilla (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study aims to identify and measure the influence of customer trust and service quality on customer loyalty in Bank Rakyat Indonesia Tapan Branch. The population of the study includes all customers of Bank Rakyat Indonesia Tapan Branch who have savings products, totaling 434 savings customers. In this study, the sample was determined using the Slovin formula, resulting in a total of 208 savings customers of Bank Rakyat Indonesia Tapan Branch. The sampling technique used was random sampling. The data analysis techniques used include descriptive statistics, classic assumptions, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that 1) Customer trust has a positive and significant effect on customer loyalty in Bank Rakyat Indonesia Tapan Branch. The coefficient value of customer trust is 0.517 with a positive direction, and the significance level (α) is 0.05 with a Sig. value of < 0.000. 2) Service quality has a positive and significant effect on customer loyalty in Bank Rakyat Indonesia Tapan Branch. The coefficient value of service quality is 0.303 with a positive direction, and the significance level (α) is 0.05 with a Sig. value of < 0.000.